Factors Associated with the Level of Knowledge of Dairy Cattle Farmers Towards Brucellosis in Kawasan Usaha Peternakan (Kunak), Bogor District - Muhammad Hilman bin Jahaluddin; Yusuf Ridwan; Chaerul Basri (Buletin Peternakan, 2020)
Level of farmer’s knowledge have an importance role in the disease prevention and control of livestock. The purpose of this research was to evaluate the level of KUNAK dairy cattle farmer’s knowledge regarding brucellosis and factors that associated to it. A series of questions were asked to the respondents regarding their knowledge of brucellosis. Respondents of 70 farmers were selected with cluster random sampling technique for this research. Data were collected through interviewing respondent using the questionnaire regarding the knowledge of brucellosis in terms of its mode of transmission, symptoms, prevention and treatment. Questionnaire was done in the form of closed question. The analysis was done using chi square test in determining the association of factors affecting level of dairy cattle farmer’s knowledge and odds ratio (OR) in determining the strength of affecting level of dairy cattle farmer’s knowledge. The general result of the level of knowledge of farmers in KUNAK were good being the majority of them were in that category. The farmers of KUNAK had a higher level of knowledge in terms of prevention and symptoms of brucellosis than mode of transmission or treatment of it. The factor that has the most significance to the level of knowledge of KUNAK dairy farmers are the ones with a working experience more than 5 years in this field with 18 times more knowledgeable than farmers with less than 5 years of working experience. The need of disease awareness programs was required for the farmers in broadening their minds towards other aspects of a disease for them to better combat the problems in their day to day business.